Full-endoscopic transpedicular discectomy (FETD) for lumbar herniations: Case report and review of the literature. (2020) - Giordan, Enrico; Del Verme, Jacopo; Coluzzi, Flaminia; Canova, Giuseppe; Billeci, Domenico
Highlights: The full-endoscopic transpedicular approach could be useful in treating lumbar migrated disc herniations or juxtafacet cysts. No documented risk of pedicle fracture after FETD. FETD showed feasibility and safety from any level from L1 to S1. Potentially FETD may be used for drainage of epidural abscesses and epidural hematomas, or in case intra-canal biopsies are needed. Abstract: Introduction: One of the most challenging occurrences in full-endoscopic surgery for lumbar disc protrusions are up-migrated or down-migrated herniations. Those occurrences are difficult to retrieve with transforaminal or interlaminar approaches. Presentation of case: We describe our experience in dealing with a right paramedian down-migrated L3-L4 disc herniation. The patient underwent full endoscopic transpedicular endoscopic discectomy (FETD), by reaming the right L4 peduncle for intracanal access and fragment retrieval. We also reviewed the recent literature to summarize the advantages of transpedicular approaches, along with current indications and contraindications for this procedure. Discussion: We highlighted how FETD is safe and feasible for down-migrated and up-migrated disc herniation showing excellent results in our patient and in the small cohorts of patients already published in the literature. Conclusion: FETD was effective in treating up-migrated and down-migrated disc herniation, as well as discal cysts, showing the feasibility and safety of the technique from any level from L1 to S1.